Systematic review of machine learning utilization within outpatient psychodynamic psychotherapy research - Dönnhoff, Ivo; Gebhardt, Nadja; Stahl-Toyota, Sophia; Simon, Joe J.; Sutcliffe, Molly; Friederich, Hans-Christoph; Nikendei, Christoph (Frontiers in psychiatry, 2023)
Introduction: Although outpatient psychodynamic psychotherapy is effective, there has been no improvement in treatment success in recent years. One way to improve psychodynamic treatment could be the use of machine learning to design treatments tailored to the individual patient's needs. In the context of psychotherapy, machine learning refers mainly to various statistical methods, which aim to predict outcomes (e.g., drop-out) of future patients as accurately as possible. We therefore searched various literature for all studies using machine learning in outpatient psychodynamic psychotherapy research to identify current trends and objectives.MethodsFor this systematic review, we applied the Preferred Reporting Items for systematic Reviews and Meta-Analyses Guidelines.Results: In total, we found four studies that used machine learning in outpatient psychodynamic psychotherapy research. Three of these studies were published between 2019 and 2021.Discussion: We conclude that machine learning has only recently made its way into outpatient psychodynamic psychotherapy research and researchers might not yet be aware of its possible uses. Therefore, we have listed a variety of perspectives on how machine learning could be used to increase treatment success of psychodynamic psychotherapies. In doing so, we hope to give new impetus to outpatient psychodynamic psychotherapy research on how to use machine learning to address previously unsolved problems.